(untitled) (Andamios, Revista de Investigación Social, 2024)
This paper studies the “Fourth World War”, a notion that emerged within the Zapatista Army of National Liberation (EZLN) during the end of the 20th century. It refers to a specific moment of capitalism: neoliberalism, against which the EZLN took up arms in 1994, although it had been organized for it since a decade before. Remarkable in its conceptual nature, World War IV is a specific moment of capitalism, against which the EZLN counterposes the organizational experience of its work areas (revolutionary praxis), as well as a political language of the anti-capitalist left (the poetics of insurgency), which together represent two dimensions of a small world, or an alternative historical possibility to the capitalism of disaster.